Relating phase transitions to pore size distributions and mechanical mortar properties in CSA-OPC-C based systems – The potential impact of delayed straetlingite formation - Wolf, Julian; Jansen, Daniel; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen (Cement and Concrete Research, 2021)
The scope of this research is to investigate the performance evolution of five ternary CSA-OPC-Cs systems. Time resolved thermodynamic modeling was employed to gain insight into changes in the volume fractions of the hydrating pastes and link these changes to trends in the pore size distributions of the mortars. Pore solution analyses were performed to investigate which hydrates have the potential to exert high crystallization pressures. In three out of five blends the resulting tensile stress exceeded the tensile strength of the materials, resulting in the occurrence of coarse pores, which could be linked to the measured compressive strengths. Two damaging crystallization processes were identified in the investigated blends. One is the continuous precipitation of ettringite at high supersaturation in a system with high anhydrite addition. The other is the delayed crystallization of straetlingite at high supersaturation and crystallization pressure in the confined environment of mature pastes.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Calcium sulfoaluminate cement; Crystallization pressure; Pore size distribution; Portland cement; Strätlingite